Service Quality: Pengembangan Instrumen Penilaian Jasa Layanan Pendidikan - Februadi, Agustinus; Mukaram (Jurnal Riset Bisnis dan Investasi, 2016)
Students’ evaluations of teaching (SETs) have been an important and the most commonly used method for evaluating teaching quality in higher education institutions. They provide feedback from students to faculty and administrators. The majority SET instruments used in Indonesia were developed based on the faculty/administrators’ knowledge and experience or adopted from other higher education institutions with or without modifications. This study aims to develop a SET instrument based on both educational theory and empirical data. Using data collected from a total of 755 students of Politeknik Negeri Bandung, the underlying dimensions and the psychometric properties of the instrument were tested. The exploratory factor analysis generated a three-factor solution. A confirmatory factor analysis was then run to cross-validate the item indicators of each factor/dimension. The reliability and validity of the instrument were also tested. The final version of SET instrument encompasses 15 items in three dimensions. The three dimensions were labeled as preparation and organization (4 items), instructional delivery (7 items), and examination and feedback (4 items). Although it was developed using student samples from Politeknik Negeri Bandung, the newly developed instrument can be used in any higher education institutions.